Engineering agricultural water resources - Lee, Teang Shui (Universiti Putra Malaysia Press, 2009)
Malaysia has a long history of experience in rice irrigation which spans from when the first scheme was built in 1892. The Kerian-Sungai Manik Irrigation Scheme which is located at Bagan Serai, Perak has a total acreage of 24000ha and the scheme is still in operation today. With the setting up of the Department of Irrigation and Drainage in 1932, there was more land for rice tilled under irrigation. In the 1960s the MADA Irrigation scheme in Kedah and Perlis, encompassing approximately 97000ha, was completed. With the inclusion of other later schemes such as the Besut Irrigation scheme in Terengganu, KETARA (5200ha,), KADA Scheme in Kelantan (26000ha), the Projek Barat Laut Scheme in Selangor (18000ha), the Seberang Perak Scheme (8500ha), PPPB Scheme in Pulau Pinang (9500ha) and the Kemasin-Semarak scheme (6500ha), make up the eight rice granaries existing today (194700ha, almost 390000ha under double cropping). Irrigation in Malaysia is almost entirely devoted to rice cultivation. Most of the irrigated rice areas in Peninsular Malaysia are located in the eight designed granaries. With recent rice supply being a bit chaotic with the sharp rise in price in the ASEAN region in early 2008, due in part to the calamities faced by some regions in the area, the Malaysian government has decided to increase its rice stockpile as well as place more lands under rice cultivation in Sabah and Sarawak. Of the available total surface water resources of Malaysia, around 75% (10 billion cubic meters per year) is for use in agriculture. Irrigation is not only the largest consumer of fresh water in terms of volume, it is also associated with comparatively low economic value, low efficiency of use (< 50%) as well as being a highly subsidized natural commodity. However, it is a must-have venture in order to give a guarantee of at least 70% of the staple food of Malaysia some figure of security. Thus, dams have to be built and maintained, water conveyance channels laid, control structures put in place for irrigation and drainage and pumps operated. All of this is just a part of the larger scheme of things, which incidentally includes the whole range of agricultural practices required in getting the grains to the markets. With the above mentioned scenario and the associated costs incurred, it is thus necessary to seek ways to better engineer and manage the water resources aspect of rice production so as to reduce the total cost of production of per unit tonne of rice grains produced in Malaysia. The total unit cost would invariably include a host of costs, but suffice to say that reducing the cost of water used in its production would help in a long way. Many have ventured to say that if the water is not used, then we still have to build dams to store it lest it just flows to the sea. These words are true in every aspect but then again, it is during times of water stresses that these dams would be a real blessing to have. So where possible dams will have to be built if not for irrigation then for the sake of domestic supplies when a real emergency crops up like the infamous 1998 El Nino phenomenon. The present climate change agenda around the globe has made all governments more aware of the need to be safe rather than to be sorry.